MARIA DUDZIKOWA, SYLWIA JASKULSKA (RED.),Twierdza. Szkoła w metaforze militarnej. Co w zamian? Seria „Kultura Szkoły”, t. 1, Wydawnictwo Wolters Kluwer, Warszawa 2016, ss. 501 - Wróbel, Alina (Studia Edukacyjne, 2020)
.